Natural Teleology in Hume's "Sceptical Solution" - Jonathan Cottrell (Journal of Modern Philosophy)
"Sceptical Solution of these Doubts" is a pivotal moment in Hume's first Enquiry: it provides his account of our warrant for inductive reasoning, and thereby explains how he can consistently move from his "Sceptical Doubts" about induction to his eventual endorsement of inductive science at the Enquiry's conclusion. However, it's hard to tell what account he means to offer: the text suggests various ideas about the source of induction's "authority", including utility, unavoidability, and reliability; it's not clear how to fit them together. This paper argues that natural teleology forms the basis of Hume's "Sceptical Solution". Inductive reasoning is a product of "custom", which has the natural function of reliably stocking our minds with true beliefs about the objects of "common life and practice". A piece of inductive reasoning is "just" or warranted if and only if it's an example of custom functioning well. On this account, induction is unwarranted if we try to use it for investigating things that lie beyond the sphere of "common life", such as the first cause of the universe. So, Hume's epistemology does not vindicate induction as a tool for natural theology. His "Sceptical Solution" grounds his injunction to limit our enquiries to the objects of common life, an aspect of his "mitigated scepticism".